Understanding Market Size and Reporting Gaps for Paediatric TB in Indonesia, Nigeria and Pakistan: Supporting Improved Treatment of Childhood TB in the Advent of New Medicines - Coghlan, Renia; Gardiner, Elizabeth; Amanullah, Farhana; Ihekweazu, Chikwe; Triasih, Rina; Grzemska, Malgorzata; Sismanidis, Charalambos (PloS one, 2015)
We sought to understand gaps in reporting childhood TB cases among public and private sector health facilities (dubbed "non-NTP" facilities) outside the network of national TB control programmes, and the resulting impact of under-reporting on estimates of paediatric disease burden and market demand for new medicines. Exploratory assessments were carried out in Indonesia, Nigeria and Pakistan, reaching a range of facility types in two selected areas of each country. Record reviews and interviews of healthcare providers were carried out to assess numbers of unreported paediatric TB cases, diagnostic pathways followed and treatment regimens prescribed. A total of 985 unreported diagnosed paediatric TB cases were identified over a three month period in 2013 in Indonesia from 64 facilities, 463 in Pakistan from 35 facilities and 24 in Nigeria from 20 facilities. These represent an absolute additional annualised yield to 2013 notifications reported to WHO of 15% for Indonesia, 2% for Nigeria and 7% for Pakistan. Only 12% of all facilities provided age and sex-disaggregated data. Findings highlight the challenges of confirming childhood TB. Diagnosis patterns in Nigeria highlight a very low suspicion for childhood TB. Providers note the need for paediatric medicines aligned to WHO recommendations. This study emphasises the impact of incomplete reporting on the estimation of disease burden and potential market size of paediatric TB medicines. Further studies on "hubs" (facilities treating large numbers of childhood TB cases) will improve our understanding of the epidemic, support introduction efforts for new treatments and better measure markets for new paediatric medicines.